Menghidupkan Kembali Budaya Baca: Peran Perempuan dan Tradisi Lokal dalam Revitalisasi Literasi di Maluku Tenggara - Afdhal, Afdhal; Kurniawati, Atik (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
This article explores the revitalization of reading culture in Southeast Maluku by highlighting the central role of women and the use of local traditions as learning instruments. The study aims to understand how literacy practices can be revived through culturally rooted, community-based approaches, and to identify the social transformations resulting from such interventions. Employing a qualitative case study method in Tual City, the research involved participatory observation, in-depth interviews with women leaders and cultural practitioners, and narrative analysis of traditional forms used in literacy activities. Findings reveal four key insights: (1) local traditions such as songs, dances, and folktales are creatively adapted as engaging and contextual tools for literacy learning; (2) women’s participation in literacy initiatives has transformed their social roles, enhancing their community status and fostering literacy-based creative economies; (3) youth increasingly view reading as a communal cultural activity rather than a school-based obligation; and (4) a gender-sensitive, culturally grounded literacy model emerged, offering replication potential in similar coastal or island communities. This study’s novelty lies in its integration of local cultural frameworks and gender perspectives in community literacy development, an area often overlooked in formal literacy discourse. It recommends adapting such models to strengthen socially grounded, inclusive approaches in the social sciences and humanities.